Synthesis two crystalline compoundsSr2-xSmxCoO4 belonging to the RUDDLESDEN-POPPER series by partial sustention of strontium (Sr) with samarium (Sm) and study their crystal structure and some physical properties. (Latakia University Journal -Basic Sciences Series, 2024)
The oxides of Sr2-xSmxCoO4 (X=1 ,1.25) were Synthesised using the ceramic method and the effect of partial sustention of Sr with Sm in crystal lattice of compound Sr2CoO4has been studied. The phases and structures were studied using powder x-ray diffraction and HRTEM(High Resolution Transmission Electron Microscopy). The compounds found to be of the 214 crystal system at n=1 of the tetragonal system of the I4/mmm space group of K2NiF4 crystal model. It was observed that the value of the parameter c decreased while the value of the parameters a,b and the volume of the cell of crystal structure increased with the increasing of the value of X. Magnetic properties were measured and curie temperature was observed between 160-200 k for sample of x=1, while antiferromagnetic behaviour was observed at 35 K for sample X = 1.25.